The role of microRNAs in oxidative stress regulation - Munjas, Jelena; Sopić, Miron; Ninić, Ana; Dobričić, Marija; Ležajić, Višnja; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
MicroRNAs (miRNAs) are small, 22-24 nucleotides long, noncoding RNAs that act as pivotal posttranscriptional regulators in various biological processes. Interaction of miRNAs with their target RNAs in most cases leads to the suppression of gene expression, by promoting degradation of RNAs or inhibiting translation. These interactions mainly occur with 3′ untranslated regions (UTR), but can also occur with 5′ UTR or with the coding part of the target RNA molecule. It is estimated that miRNAs regulate more than 30–60% of protein coding genes in the human genome. Oxidative stress refers to an imbalance between reactive oxygen species (ROS) generation and body's capability to detoxify the reactive mediators or to fix the relating damage. ROS can regulate miRNA transcription, maturation, and function. ROS directly modulate the activity of vital proteins that control posttranscriptional events in the biogenesis of miRNAs (Di George critical region-8 protein; Dicer). A certain group of transcription factors involved in the regulation of miRNA expression is upregulated under oxidative stress and directly activates the transcription of a subset of miRNAs. ROS have been directly implicated in epigenetic alternations such as DNA methylation and histone modifications that control specific microRNA transcription. On the other hand, miRNAs may in turn modulate the redox signalling pathways, altering their integrity, stability, and functionality, thus contributing to the pathogenesis of multiple diseases: cancer, neurodegenerative diseases, diabetes mellitus, ROS-related cardiac diseases, including myocardial infarction, ischemia/reperfusion injury, cardiac hypertrophy and heart failure, and are also considered as potential therapeutic targets and novel diagnostic tools.